Multi-Modal Optical Imaging and Combined Phototherapy of Nasopharyngeal Carcinoma Based on a Nanoplatform - Lin Y; Qiu T; Lan Y; Li Z; Wang X; Zhou M; Li Q; Li Y; Liang J; Zhang J (International Journal of Nanomedicine, 2022)
Yanping Lin,1,* Ting Qiu,2,* Yintao Lan,3,* Zhaoyong Li,1 Xin Wang,4 Mengyu Zhou,3 Qiuyu Li,1 Yao Li,1 Junsheng Liang,1 Jian Zhang3,4 1Department of Radiology, DongGuan Tungwah Hospital, DongGuan, Guangdong, 523000, People’s Republic of China; 2Department of Radiology, Zhuhai People’s Hospital (Zhuhai Hospital Affiliated with Jinan University), Zhuhai, Guangdong, 519000, People’s Republic of China; 3Department of Biomedical Engineering, School of Basic Medical Sciences, Guangzhou Medical University, Guangzhou, Guangdong, 511436, People’s Republic of China; 4Department of Oncology, The Sixth Affiliated Hospital of Guangzhou Medical University, Qingyuan People’s Hospital, Qingyuan, Guangdong, 511500, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhang; Junsheng Liang, Email jianzhang@gzhmu.edu.cn; 2581892622@qq.comAbstract: Nasopharyngeal carcinoma (NPC) is a common malignant tumor of the head and neck with a high incidence rate worldwide, especially in southern China. Phototheranostics in combination with nanoparticles is an integrated strategy for enabling simultaneous diagnosis, real-time monitoring, and administration of precision therapy for nasopharyngeal carcinoma (NPC). It has shown great potential in the field of cancer diagnosis and treatment owing to its unique noninvasive advantages. Many Chinese and international research teams have applied nano-targeted drugs to optical diagnosis and treatment technology to conduct multimodal imaging and collaborative treatment of NPC, which has become a hot research topic. In this review, we aimed to introduce the recent developments in phototheranostics of NPC based on a nanoplatform. This study aimed to elaborate on the applications of nanoplatform-based optical imaging strategies and treatment modalities, including fluorescence imaging, photoacoustic imaging, Raman spectroscopy imaging, photodynamic therapy, and photothermal therapy. This study is expected to provide a scientific basis for further research and development of NPC diagnosis and treatment.Keywords: nasopharyngeal carcinoma, optical imaging, phototherapy, nanoparticle